Analisis Kesalahan Siswa dalam Mengerjakan Soal Cerita dalam Materi Statistika SMP Negeri 1 Binjai Kelas VIII - Sarasanty, Maurin Putri; Firdaus, Muliawan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to describe the types of errors or causes of students solving statistics questions and describe students’ difficulties in solving statistics story problems. This type of research is descriptive qualitative research which uses 3 research subjects. The research instruments used were test sheets, interview guidelines, and observation sheets. After the instrument is declared valid by the validator, a field trial is then carried out to analyze student errors. The research results showed that: Based on the results of the student answer sheets and the results of interviews with the 3 subjects, 3 errors were found in solving statistics story questions, namely conceptual errors, principle errors and procedural errors. The student who experienced the most errors was the student with the initials MA, and the student who experienced the fewest errors in solving statistics story problems was the student with the initials AD. The factor that causes students’ errors and difficulties in solving word problems is that subjects with conceptual errors do not understand the concept of the mean and do not write down the definition of the mean. Furthermore, subjects with principle errors are subjects who do not pay attention to the prerequisites for using formulas because they forget how to do the questions. Then subjects with procedural errors are subjects who are less careful when calculating the final answer because of the subject’s habit of not checking again when they have received the answer.